Increasing abundance of soil fungi is a driver for (15)N enrichment in soil profiles along a chronosequence undergoing isostatic rebound in northern Sweden. - Wallander, Håkan; Mörth, Carl-Magnus; Giesler, Reiner (Oecologia, 2009)
Soil organic material (SOM) is usually enriched in (15)N in deeper soil layers. This has been explained by discrimination against the heavier isotope during decomposition or by the accumulation of (15)N-enriched microbial biomass versus plant biomass in older SOM. In particular, ectomycorrhizal (EM) fungi have been suggested to accumulate in old SOM since this group is among the most (15)N-enriched components of the microbial community. In the present study we investigated the microbial community in soil samples along a chronosequence (7,800 years) of sites undergoing isostatic rebound in northern Sweden. The composition of the microbial community was analyzed and related to the delta(15)N and delta(13)C isotope values of the SOM in soil profiles. A significant change in the composition of the microbial community was found during the first 2,000 years, and this was positively related to an increase in the delta(15)N values of the E and B horizons in the mineral soil. The proportion of fungal phospholipid fatty acids increased with time in the chronosequence and was positively related to the (15)N enrichment of the SOM. The increase in delta(13)C in the SOM was much less than the increase in delta(15)N, and delta(13)C values in the mineral soil were only weakly related to soil age. The C:N ratio and the pH of the soil were important factors determining the composition of the microbial community. We suggest that the N being transported from the soil to aboveground tissue by EM fungi is a driver for (15)N enrichment of soil profiles.